2004
DOI: 10.1158/0008-5472.can-04-1627
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Targeting Transforming Growth Factor-β Enhances NKG2D-Mediated Antiglioma Immune Response, Inhibits Glioma Cell Migration and Invasiveness, and Abrogates TumorigenicityIn vivo

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
224
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 272 publications
(234 citation statements)
references
References 43 publications
8
224
2
Order By: Relevance
“…The loss of invasiveness of LNT-229 cells stably expressing small interfering TGF-b 1/2 RNA has been linked to the loss of MMP activity. 23 Appropriate control experiments using antibodies against TGF-b and a MMP inhibitor confirmed that the proinvasive effect of BCL-x L entirely depended on these molecules (Figures 4a and 6b). These data do not differentiate between the necessity for TGF-b 2 in baseline and BCL-x L -induced invasiveness.…”
Section: Discussionmentioning
confidence: 68%
“…The loss of invasiveness of LNT-229 cells stably expressing small interfering TGF-b 1/2 RNA has been linked to the loss of MMP activity. 23 Appropriate control experiments using antibodies against TGF-b and a MMP inhibitor confirmed that the proinvasive effect of BCL-x L entirely depended on these molecules (Figures 4a and 6b). These data do not differentiate between the necessity for TGF-b 2 in baseline and BCL-x L -induced invasiveness.…”
Section: Discussionmentioning
confidence: 68%
“…Excessive proliferation, diffuse infiltration of surrounding brain tissue, and suppression of antitumor immune surveillance contribute to the malignant phenotype of gliomas (Weller and Fontana, 1995). Silencing of TGF-b expression by small interfering RNA (siRNA) technology has been reported to abrogate glioma cell tumorigenicity in vivo (Friese et al, 2004).…”
Section: Tgf-b and Neural Stem Cells (Nscs)mentioning
confidence: 99%
“…9 Recent NKG2D regulation studies showed that many cytokines influence NKG2D expression on CD8 C T and NK cells, including the NKG2D-promoting cytokines interleukin (IL)-2, IL-7, and IL-12 [10][11][12] ; the NKG2D-suppressing cytokines IL-4 and transforming growth factor-b; and interferon-g, at high levels. 13,14 However, the mechanisms of NKG2D regulation on CD8 C T cells remain poorly investigated.…”
Section: Introductionmentioning
confidence: 99%